Pengaruh Pembayaran Digital Terhadap Efektivitas Kebijakan Moneter - Lewa, Muhammad Juwantho; Asrina, Asrina (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of digital payments on the effectiveness of monetary policy in Indonesia during the period of rapid financial digitalization. The main focus lies on the relationship between the expansion of digital payment instruments such as e-wallets, mobile banking, and QRIS and core monetary policy variables, including interest rates, money supply (M2), and inflation stability. A descriptive-quantitative approach was used based on secondary data from Bank Indonesia, BPS, and related institutions. The results show that the rapid adoption of digital payments affects the transmission mechanism of monetary policy by increasing the velocity of money, shifting banking intermediation, and altering public behavior toward money demand. Digital payments tend to weaken the interest rate channel but strengthen the expectations and liquidity channels. These findings highlight the need for the central bank to adapt its policy framework to maintain monetary stability in an increasingly digital economy